Validation of a mutant of the pore-forming toxin sticholysin-I for the construction of proteinase-activated immunotoxins - Penton, David; Perez-Barzaga, Victor; Diaz, Iscel; Reytor, Mey L.; Campos, Javier; Fando, Rafael; Calvo, Loany; Cilli, Eduardo Maffud [UNESP]; Morera, Vivian; Castellanos-Serra, Lila R.; Pazos, Fabiola; Lanio, Maria E.; et al. (Oxford University Press, 2011)
The use of pore-forming toxins from sea anemones (actinoporins) in the construction of immunotoxins (ITs) against tumour cells is an alternative for cancer therapy. However, the main disadvantage of actinoporin-based ITs obtained so far has been the poor cellular specificity associated with the toxin's ability to bind and exert its activity in almost any cell membrane. Our final goal is the construction of tumour proteinase-activated ITs using a cysteine mutant at the membrane binding region of sticholysin-I (StI), a cytolysin isolated from the sea anemone Stichodactyla helianthus. The mutant and the ligand moiety would be linked by proteinase-sensitive peptides through the StI cysteine residue blocking the toxin binding region and hence the IT non-specific killing activity. To accomplish this objective the first step was to obtain the mutant StI W111C, and to evaluate the impact of mutating tryptophan 111 by cysteine on the toxin pore-forming capacity. After proteolysis of the cleavage sequence, a short peptide would remain attached to the toxin. The next step was to evaluate whether this mutant is able to form pores even with a residual peptide linked to cysteine 111. In this work we demonstrated that (i) StI W111C shows pore-forming capacity in a nanomolar range, although it is 8-fold less active than the wild-type recombinant StI, corroborating the previously reported importance of residue 111 for the binding of StI to membranes, and (ii) the mutant is able to form pores even with a residual seven-residue peptide linked to cysteine 111. In addition, it was demonstrated that binding of a large molecule to cysteine 111 renders an inactive toxin that is no longer able to bind to the membrane. These results validate the mutant StI W111C for its use in the construction of tumour proteinase-activated ITs.
Keywords: actinoporin; immunotoxin; pore-forming toxin; sea anemone cytolysin; sticholysins